Assessment of Factors Affecting the Return on Equity (ROE) in Banks by the Example of Ameriabank CJSC - Harutyunyan, Gayane («Տնտեսագետ» հրատ․)
The article is devoted to the definition, analysis, and evaluation of the main indicators of profitability in banks. It is no secret that profitability is one of those simple indicators that allows setting a comprehensive picture of the effectiveness of the bank's activities. With its help, both external and internal beneficiaries evaluate competitive advantages and possible changes in the development of the bank's activities and, as a result, make corporate decisions. On our part, an attempt was made to analyze the main profitability indicators of Ameriabank CJSC (hereinafter the bank). Return on Equity (ROE) and Return on Assets (ROA) for 37 quarters (from the 4th quarter of 2014 to the 4th quarter of 2023) and the main indicators affecting the latter were analyzed. For this purpose, more than 20 variables were identified and calculated, classified into external and internal indicators. The analysis was carried out in three main directions: 1. Key indicators (Spread, Net Interest Margin (NIM)) used in international practice to disclose the policies pursued by banks were calculated and their dynamics were monitored, 2. A DuPont factor analysis was performed to find out which factors primarily influenced the bank's policy, 3. A regression model was built to understand exactly what changes in indicators will make it possible to increase profitability. As a result, a regression correlation model was built, which made it possible to accurately predict the bank's ROE for the next period. The result applies to the bank when the latter wants to change its policy.
Keywords: Finance